Efficacy of Baricitinib in Patients with Refractory Adult-Onset Still’s Disease - Ziyi Sun; Rongqi Li; Yingai Wang; Feng Han; Wei Wei; Xin Li (Drugs in R&D, 2023)
Abstract Background and Objective Adult-onset Still’s disease (AOSD) is an idiopathic systemic inflammatory disease of unknown aetiology. Some patients exhibit resistance to conventional treatment during long-term therapy. Janus kinase inhibitors (JAKinibs) may contribute to the improvement in AOSD symptoms via the JAK–signal transducer and activator of transcription (STAT) pathway. We aimed to explore the efficacy and safety of baricitinib in patients with refractory AOSD. Methods Patients were enrolled if they fulfilled the Yamaguchi AOSD classification criteria in China between 2020 and 2022. All patients were recognized as having refractory AOSD and were treated with oral baricitinib at a dosage of 4 mg once daily. A systemic score and prednisone dosage were used to evaluate the efficacy of baricitinib at months 1, 3, and 6 and at the last follow-up visit. The safety profiles were recorded and analysed at every assessment. Results Seven female patients with refractory AOSD received baricitinib. The median age was 31 (IQR 10) years. Treatment was terminated in one patient due to progressive macrophage activation syndrome (MAS). Others continued baricitinib treatment until the last assessment. The systemic score decreased significantly at 3 months (p = 0.0216), 6 months (p = 0.0007), and the last follow-up visit (p = 0.0007) compared with baseline. One month after the initiation of baricitinib, the rates of improvement in fever, rash, sore throat, and myalgia symptoms were 71.4% (5/7), 40% (2/5), 80% (4/5), and 66.7% (2/3), respectively. Five patients remained symptom-free at the last follow-up visit. In most patients, their laboratory values had returned to normal by the last follow-up visit. A significant reduction in the levels of C-reactive protein (CRP) (p = 0.0165) and ferritin (p = 0.0047) was observed at the last visit compared with baseline. The daily prednisolone dosage significantly decreased from 35.7 ± 15.1 mg/day at baseline to 8.8 ± 4.4 mg/day by month 6 (p = 0.0256), and it was 5.8 ± 4.7 mg/day at the last assessment (p = 0.0030). Leukopenia due to MAS was noted in one patient. Except for mild abnormalities in lipid parameters, no other severe adverse events occurred during follow-up. Conclusions Our findings suggest that baricitinib therapy could provide rapid and durable clinical and laboratory improvement in patients with refractory AOSD. Treatment seemed to be well tolerated by these patients. The long-term efficacy and safety of baricitinib therapy for AOSD should be assessed further in prospective controlled clinical trials in the future. Trial Registration Trial registration number (TRN): ChiCTR2200061599. Date of registration: 29 June 2022 (retrospectively registered).